2022
DOI: 10.1186/s12866-022-02445-w
|View full text |Cite
|
Sign up to set email alerts
|

Application of cotton straw biochar and compound Bacillus biofertilizer decrease the bioavailability of soil cd through impacting soil bacteria

Abstract: Background Cd seriously threatens soil environment, remedying Cd in farmland and clearing the response of soil environment to modifiers in Cd-contaminated soils is necessary. In this study, the effects of cotton straw biochar and compound Bacillus biofertilizer used as modifiers on the biochemical properties, enzyme activity, and microbial diversity in Cd-contaminated soils (1, 2, and 4 mg·kg−1) were investigated. Results The results showed that bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 63 publications
2
2
0
Order By: Relevance
“…S3a). Similar observations were also reported (Zhu et al, 2022a). An increased soil pH stimulates the formation of more precipitation complexes, which enhances Cd passivation and decreases Cd bioavailability (Quilliam et al, 2013) (Bandick and Dick, 1999).…”
Section: Effects Of Strain An-b15 and Biochar On CD Speciation Ph And...supporting
confidence: 92%
See 1 more Smart Citation
“…S3a). Similar observations were also reported (Zhu et al, 2022a). An increased soil pH stimulates the formation of more precipitation complexes, which enhances Cd passivation and decreases Cd bioavailability (Quilliam et al, 2013) (Bandick and Dick, 1999).…”
Section: Effects Of Strain An-b15 and Biochar On CD Speciation Ph And...supporting
confidence: 92%
“…The combination of biochar and microorganisms combines the merits of the two methods and avoids the de ciency caused by the use of biochar or bacteria alone, thus achieving e cient reduction in Cd motility by direct immobilization of Cd, improvement of soil quality and the survival of exogenous bacteria, and enrichment of special microbes (Ma et al, 2020;Qi et al, 2021). Among these bacteria, biochar and species within the genus Bacillus have been reported to effectively reduce Cd mobility and increase soil pH and enzyme activities (Mei et al, 2022;Zhu et al, 2022a). As previously stated, the mechanisms involving Cd immobilization by biochar or bacteria alone have been clearly studied.…”
Section: Introductionmentioning
confidence: 99%
“…Significant differences were observed between substrates for all soil fertility indicators (Table 4). The use of bovine manure in the substrate, the inoculation of cotton seeds with the N 2 -fixing bacterium A. brasilense, and the application of anaerobically-made biofertilizer caused a significant improvement in the indicators of soil acidity, availability of essential mineral nutrients, and organic matter compared with poor soil fertilized with chemical fertilizers, as also found in other studies (SHARMA; VASUDEVA, 2005;LIMA et al, 2007;SCHWEINSBERG-MICKAN;MÜLLER, 2009;OBIA et al, 2015;GALINDO et al, 2017;SILVA et al, 2019;ZHU et al, 2022). Moreover, diazotrophic bacteria also contribute to increase the soluble P available to plants in the soil (SILVA et al, 2006;BUSATO et al, 2012).…”
Section: Resultssupporting
confidence: 68%
“…Duan et al [55] studied the effect of biochar addition to salt-affected soil on water movement and found that the transition rate of the soil moisture increased after biochar supplementation to the soil. From another view, [56] found that the application of cotton stalk biochar increased the soil EC around 45% compared to the control, but according to this study it was found that the application of cotton biochar caused a migration of salts through the soil profile in both seasons, recording 22.37% and 23.87% in maize and wheat seasons compared to 21.14% and 22.17% with the control treatment, whereas the modified cotton biochar CSMB treatment reached 23.78% and 31.36% in maize and wheat plants, respectively. Overall changes in ESP were observed with the application of biochar.…”
Section: Soil Characteristicsmentioning
confidence: 99%